Thermal inactivation of the wine spoilage yeasts dekkera/brettanomyces - Couto, José António (2005)
The heat resistance of three strains of Dekkera/Brettanomyces (Dekkera anomala PYCC 5153, Dekkera bruxellensis PYCC 4801 and Dekkera/Brettanomyces 093) was evaluated at different temperatures between 32.5 and 55ºC. Thermal inactivation tests were performed in tartrate buffer solution (pH 4.0) and in wines. In the studies employing buffer as the heating menstruum, measurable thermal inactivation began only at temperatures of 50ºC. When heating was performed in wine, significant inactivation begins at 35ºC. Subsequent thermal inactivation tests were performed in buffer at various levels of pH, ethanol concentration, and various phenolic acids. Results from experiments in buffer with added ethanol suggest that the greater heat sensitivity shown in wines can be largely attributed to ethanol, although potentiation of this effect might be due to the phenolic content, particularly from ferulic acid. In the range of pH values tested (2.5–4.5), this factor had no influence in the heat inactivation kinetics. Relevant data, in the form of D and Z values calculated in the various environments, potentially useful for the establishment of regimes of thermal control of Dekkera/Brettanomyces yeasts in wine and contaminated equipment is presented.